Trend and Determinants of Early Postnatal Care in Nepal with a Focus on Women’s Autonomy - Aryal, Yeshoda (Kutumbha vani, 2024)
Nepal has made significant strides in improving maternal and child health, notably reducing mortality rates over recent decades. However, challenges persist in meeting the maternal and newborn health targets outlined in the Sustainable Development Goals. Postnatal care is essential for the survival and well-being of both mothers and newborns, yet there is limited research on this topic in Nepal. This study aims to assess trends in early postnatal care coverage and analyze the factors influencing service uptake focusing on women’s autonomy. Using data from the Nepal Demographic and Health Surveys for 2011, 2016, and 2022, which included 10,991 mothers aged 15-49 with at least one live birth, the study revealed significant improvements in postnatal care coverage. The percentage of mothers receiving care within 48 hours increased from 43% in 2011 to 56% in 2016, reaching 72% in 2022. Despite this progress, 28% of mothers and newborns still lack timely postnatal care, which is crucial for their survival and well-being. Regression analysis indicated that women with greater decision-making autonomy are significantly more likely to receive postnatal care (adjusted OR 1.216, P < 0.01), even when accounting for socio-demographic factors. The study highlighted disparities in postnatal care coverage based on age, caste/ethnicity, education, occupation, province, urbanrural residence, wealth, and family size. These findings emphasize the need for targeted interventions to empower women and tailor maternal health programs to address the specific needs. Future research should focus on evaluating complete postnatal care coverage, assessing care quality, and exploring interventions to strengthen maternal health care.